The Approach of ACARS Data Encryption and Authentication - Meng Yue; Xiaofeng Wu (2010 International Conference on Computational Intelligence and Security, 2010)
With the increasing number of aircraft, the airlines and civil aviation organization are relying on ACARS (Aircraft Communications Addressing and Report System) for air traffic and control. Unfortunately, automated information exchange between aircraft and ground entity also increase the system vulnerability and may severely impacts the safety of a flight. This paper introduce a End-to-End architecture which employ message encryption and authentication to protect the security between aircraft and airlines and thus permit ACARS data link messages to be exchanged in a secure manner.